Celebrity death certificates, 3 - Steen, M. F. (Michael F.), 1946- (McFarland & Company, Inc., Publishers, 2010)
"From previous editions: "fascinating ... recommend[ed]"--Classic Images; "fascinating ... excellent job ... informative"--Big Reel; "fascinating ... unique"--ARBA; "definitely ... of interest to Hollywood trivia buffs"--Valley Scene Magazine; "a unique reading experience ... intriguing"--Associated Content; "Mike Steen REALLY knows where the bodies are buried in Hollywood ... fascinating"--National Enquirer; "definitely ... of interest to Hollywood trivia buffs"--Bookstew"--Provided by publisher